EFEKTIVITAS DOSIS DESINFEKTAN FENOL TERHADAP ANGKA KUMAN PADA LANTAI RUANG RAWAT INAP RSUD TUGUREJO KOTA SEMARANG - Ariani, Ariani; Setiani, Onny; Joko, Tri (Jurnal Kesehatan Masyarakat (Undip), 2015)
One of hospital sanitary efforts is surface disinfection with chemical compound. Disinfection is done through floor mopping with phenolic disinfectant. Disinfectant dose is a factor which determined to how its disinfectant works. Till now, there hasn’t been known about the effective dose of phenolic disinfectant to decrease bacteria count on the floor of wards at Tugurejo Public Hospital in Semarang city.The purpose of this research is to know the effectiveness of phenol disinfectant dose to bacteria count in the treatment room. The method that is used for this research is quasi experiment pre-test post-test control group design. The independence variable is phenol disinfectant doses, which are 6ml, 8ml, 10ml, and 12 ml. Meanwhile, dependence variable is bacteria count on the floor in the treatment room at tugurejo public hospital. Description and narration of bacteria count  are used for univariate analysis. Statistic test of paired sample t-test, one way annova and LSD are used for bivariate analysis. The results of this research revealed that in the floor mopping with 6ml dose of phenol disinfectant, the bacteria count decreased to 7,17 %, in 8ml dose it’s 58,35 %, in 10 ml dose it’s 65,30 %, in 12 ml dose it’s 69,27 %. The result of one way annova, revealed that p-value is 0,000. It means that there is a difference of average bacteria count between phenol disinfectant dose of 6ml, 8ml, 10ml, and 12 ml. Based on LSD test, it revealed that effectiveness of 8ml, 10 ml, and 12 ml phenol disinfectant to bacteria count are even. The conclusions of this research are there’s an influence of phenol disinfectant dose to bacteria count on the floor and the most effective phenol dose to be used is 6 ml. The advice for health workers are to enforce the provision about appropriate disinfectant dose for floor mopping and make a guidance to cleaning services who are in charge of the wards.